2022
DOI: 10.1007/s10508-022-02292-w
|View full text |Cite
|
Sign up to set email alerts
|

Love in the Time of Corona: Predicting Willingness to Engage in Sexting During the First COVID-19-Related Lockdown

Abstract: When the COVID-19 pandemic began, in early 2020, lockdowns limited the options for physical intimacy and many resorted to technology-mediated forms of intimacy such as sexting. However, it is unclear what predicted willingness to engage in sexting during the lockdown. The present study filled this gap by investigating COVID-19-related social isolation, privacy concerns, age, and gender as predictors of willingness to engage in sexting. We further examined an interaction of COVID-19-related social isolation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…As regards gender, past literature suggests that women would be less prepared to engage in sexting behavior, due to prevailing sexual mores, according to which women feared much heavier social consequences than men ( Ringrose et al, 2013 ; Salter, 2016 ; Setty, 2019 ), but it was shown that, during the pandemic, this bias was not found in the female sample. For example, Thomas et al (2022) found no effect of gender on willingness to engage in sexting, probably due to sexual needs that had arisen in the wake of COVID-19 restrictions. Recent studies indicated an increase in sexting activities during the first phase of the pandemic ( Gabster et al, 2022 ), suggesting that it could have had a role in coping with pandemic difficulties, such as sexual and couple satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…As regards gender, past literature suggests that women would be less prepared to engage in sexting behavior, due to prevailing sexual mores, according to which women feared much heavier social consequences than men ( Ringrose et al, 2013 ; Salter, 2016 ; Setty, 2019 ), but it was shown that, during the pandemic, this bias was not found in the female sample. For example, Thomas et al (2022) found no effect of gender on willingness to engage in sexting, probably due to sexual needs that had arisen in the wake of COVID-19 restrictions. Recent studies indicated an increase in sexting activities during the first phase of the pandemic ( Gabster et al, 2022 ), suggesting that it could have had a role in coping with pandemic difficulties, such as sexual and couple satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…The lockdown limited the options for physical intimacy, and the prevalence of sending nudes may, therefore, have increased the need for sending nudes in some groups. According to Thomas et al ( 2022 ), younger men and women may have used sending nudes to cope with the unprecedented COVID-19-related situation.…”
Section: Discussionmentioning
confidence: 99%
“…Given the unique circumstances of the pandemic, however, sexting may have served as an alternative to in-person sexual behavior and thus may be linked to relationship satisfaction. In fact, young adults who felt isolated due to the pandemic were more willing to engage in sexting (Thomas et al, 2022). Thus, we explore whether sexting was associated with LGBTQ+ students’ relationship satisfaction during the pandemic.…”
Section: Introductionmentioning
confidence: 99%